The eternity portfolio, illuminated - Gotthardt, Alan. (Sisters, Oregon : Deep River Books, 2015)
In The Eternity Portfolio, CPA and financial advisor Alan Gotthardt combines biblical teaching with modern investment-portfolio theory and offers how-tos for strategic, satisfying giving. He expands and illuminates his work with guest commentary from seven other world-class kingdom investors in this Illuminated Editon. Perfect for Christians everywhere who want to invest their money for lasting results and provides the framework and tools they need to create their own step-by-step action plan.
Faithful managers : investing with their values -- The ultimate investment -- The eternity portfolio -- -- Funding the portfolio, part 1 : how much is enough for now? -- Funding the portfolio, part 2 : how much is enough for good? -- God's asset allocation -- Making wise investments -- Passing the baton : a legacy that outlasts you -- The seven golden keys to investing for eternity.
Includes bibliographical references (pages 269-272).
Keywords: Christian stewardship